Chemical Reaction Effects on the Flow of Titanium Dioxide–Water in a Mixed Convective Nanofluid along an Inclined Plate in a Porous Medium - Md. Nasir Uddin; Kakali Chowdhury; Jannatul Ferdows Mim (Advances in Mathematical Physics)
An inclined plate is being approached by a mixed convective boundary layer nanofluid flow of titanium dioxide–water through a porous medium. A numerical analysis has been done to investigate the effects of chemical reactions on the considered nanofluid flow. With the aid of a system of governing partial differential equations, a set of nonlinear ordinary differential equations for taking into consideration nanofluid flow have been derived using appropriate matching transformations. The Runge–Kutta method, as well as the Nachtsheim and Swigert Shooting method, is applied to numerically resolve the group of subsequent nondimensionalized equations. The associated numerical result was then successfully compared with the available published literature in a few unique, limited circumstances. Based on the considered nanofluid flow characteristics for heat as well as mass transfer, the effects of the Schmidt number, the permeability, and the chemical reaction parameters of the titanium dioxide–water nanofluid flow have been examined, assessed, and presented for velocity in conjunction with the local skin friction coefficient, temperature in conjunction with the local Nusselt number, as well as concentration in conjunction with the local Sherwood number. Numerical results reveal that the local Sherwood number Sh, as well as the local Nusselt number Nux, increase, whereas the local skin friction coefficient Cf decreases due to the increase in the chemical reaction parameter Krp.